Homoconjugalidade masculina, revelação e redes sociais: um estudo de caso - Defendi, Edson Luiz (2010)
This study aimed to understand how the process of disclosure of gay male couples reflects in the construction of the couple's social network and the dynamics of their relationships. For the construction of this study we conducted a qualitative and interpretive research emphasizing the socially constructed nature of reality and the importance of understanding the phenomenon in a contextualized and systemic way. The methodological strategy adopted for this work was the case study, without exhausting it and/or making generalizations, but only considering the uniqueness and richness of the chosen case. The instruments used were a semi-structured interview, the Map of Social Network proposed by Sluzki (1997) and the Timeline of the couple. We interviewed two gay male couples and for purposes of this study a wealthy couple with diversity of information was chosen. We had three meetings with this couple an individual meeting with each member of the dyad and a joint meeting. The analysis and the results of the research show that building a gay male couple relationship requires of its members a sense of identity and clarity as to the desire to live together. For the participating couple, disclosing does not necessarily mean that they must tell everyone of their social network about their relationship. Living as a couple, living together, being always socially together and also rely on each other, preserving a certain personal life privacy are ways of socially legitimate their relationship and turn it visible. Despite the difference in meaning and the consequent attitudes about disclosing or not their relationship, each member of the couple respects the other's position and that does not generate conflicts in their relationship. Disclosing brings people closer, keeping their relationship secret builds boundaries between the couple and their social network. These limits are more visible in the family of origin, reflecting on the rejection of the couple, and when the family of one of the participants incorporates the couple but with little intimacy between the parties. Friendly relationships offer more intimacy and closeness to the couple when they are aware about their condition, and at work, the more comfortable coexistence between the couple and their colleagues is when they do not disclose their gay male couple condition. We believe that the knowledge of such features of gay male couples is relevant to the work in the mental health area